ANALYSIS OF MARKETING STRATEGIES IN THE CULINARY BUSINESS TO IMPROVE COMPETITIVENESS AT THE NEW DONA DONY STORE - Sri Wahyuni; Marhawati, Muhammad Jufri, Asmayanti, Sumiati Tahir (CV. Adiba Aisha Amira, 2025)
This research aims to analyze the 7P marketing strategy (Product, Price, Place, Promotion, People, Process, and Physical Evidence) in the culinary business, specifically at Toko Dona Dony Baru, and how these strategies affect the store's competitiveness. The research method used is a qualitative method with a case study approach. Data were collected through in-depth interviews with the store owner, direct observation, and documentation. The research results show that Toko Dona Dony Baru implements the 7P elements in its marketing strategy, with an emphasis on product quality, product packaging, product variety, affordable prices, price-quality equivalence, competitive pricing with similar products, consumer accessibility, strategic business location, sales promotion, public relations with online and direct marketing publicity, employee attitude in serving customers, adequate equipment, room appearance, and company layout. These factors significantly contribute to the improvement of the store's competitiveness in the competitive culinary market. This research provides practical insights for culinary business operators on the importance of implementing the 7P marketing strategy to achieve competitive advantage.